Sociological Analysis of Family through the Lense of Ramayana - Dr. Twinkle Sanghavi (Samā Jiva Jnānam (International Journal of Social Studies), 2025)
This research article examines the concept of family in Valmiki’s Ramayana, focusing on its cultural, moral, and social importance. The study uses qualitative textual analysis along with sociological theories such as role theory, symbolic interactionism, and functionalism to look at family duty, gender roles, sibling connections, emotional work, and the passing down of values. By analysing key characters and events, including Rama’s exile, Sita’s moral choices, Lakshmana’s loyalty, and Bharata’s renunciation, the article shows that the Ramayana presents family not as a fixed ideal but as a complex moral institution based on dharma (duty) and resilience. It also explores how women contribute to and challenge family structures and highlights the concept of extended and chosen families beyond biological ties. The findings suggest that the epic offers timeless lessons on sacrifice, forgiveness, and ethical decision-making that are still relevant to today’s family issues. The study concludes that the Ramayana, while grounded in tradition, provides a dynamic and thoughtful view of family life, one that continues to spark discussions across generations and cultures.